EVOLUTION OF THE AGRICULTURAL LAND FUND OF THE REPUBLIC OF MOLDOVA IN THE CONTEXT OF THE TRANSITION FROM THE HYPER-CENTRALIZED ECONOMIC SYSTEM TO THE MARKET ECONOMY - Viorel TURETCHI; Tatiana TURETCHI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Efficient management of the agricultural land fund is one of the basic priorities of each state. The given resource represents the totality of the agricultural lands within a territorial-administrative unit. The Republic of Moldova, having a specific geopolitical position, during the twentieth century was subjected to various areas of influence, which imposed their own views on how to manage the land. As a result, all the political and administrative changes involved the fundamental reform of the agricultural sector and, directly, of the agricultural land fund. The paper is a reflection of the evolution of the country's land fund in the context of social and political change during the XX-XI century. The analysis of that period showed that the only viable and efficient method of managing the land fund agricultural is private property based on the implementation of modern production technologies. The general research methods (empirical and theoretical methods) were used in the process of elaborating this report, the analysis of statistical data reflecting the evolution of the national land fund as well as of the agricultural land areas were widely applied.